(untitled) (Research, Society and Development, 2024)
Introduction: Major Depressive Disorder globally affects around 5% of the population, with a complex etiology involving interactions between the brain, mind and environment. Around 50% of cases do not respond to standard pharmacological treatment, highlighting the need for innovative therapeutic approaches. Objective: This research aims to explore the therapeutic potential of psilocybin in major depressive disorder, analyzing its interaction with serotonergic receptors, and investigating the effects of the substance on brain connectivity. Methodology: This is a narrative review of the literature, searching for articles in the Pubmed database. The selection considered inclusion criteria, resulting in a sample of articles relevant for the analysis. Results and Discussion: The results reveal that psilocybin, a serotonergic agonist, induces long-lasting and rapid therapeutic effects, modulating receptors such as 5-HT2AR. The substance promotes neuroplasticity, improving brain connectivity and reducing depressive symptoms. Conclusion: The effectiveness of psilocybin in treating depression points to an innovative understanding of neurobiological mechanisms. Its ability to induce neuroplasticity suggests promising implications, highlighting the safety of combination with traditional therapies.